Lymphocytic interstitial pneumonia and pulmonary embolism in a patient with tetralogy of Fallot and common variable immunodeficiency: is there any link?. Issue 5 (28th April 2008) - Valdivia-Arenas, M A; Sood, N
Abstract : We report the simultaneous occurrence of lymphocytic interstitial pneumonitis and pulmonary embolism in a patient with tetralogy of Fallot and common variable immunodeficiency. An explanation based on the pathogenesis of these diseases is proposed to explain this "unfortunate coincidence".